2007
DOI: 10.1111/j.1468-3083.2007.02227.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of facial aesthetics in surgical patients with basal cell carcinoma

Abstract: It is recommended to administer preoperatively a short questionnaire in which perceptions related to facial aesthetics are included. In doing so, physicians will become more familiar with the aesthetic problems patients might have regarding their afflicted facial site. Ultimately, it may help physicians in deciding whether patients will benefit from additional cosmetic procedures after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 8 publications
1
29
0
3
Order By: Relevance
“…27 Through a process of item generation and refinement, a 15-item questionnaire was constructed with three subscales; emotional (seven items), social (five items) and appearance (three items). 9 The concern for facial scarring or disfigurement was also regularly reported in an openended survey administered to NMSC patients regarding their QOL. 5 The SCI scores demonstrated that patients who were women, <50 years old and in employment experienced a greater impact on their QOL.…”
Section: Sf-36 Fact-g Vasmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Through a process of item generation and refinement, a 15-item questionnaire was constructed with three subscales; emotional (seven items), social (five items) and appearance (three items). 9 The concern for facial scarring or disfigurement was also regularly reported in an openended survey administered to NMSC patients regarding their QOL. 5 The SCI scores demonstrated that patients who were women, <50 years old and in employment experienced a greater impact on their QOL.…”
Section: Sf-36 Fact-g Vasmentioning
confidence: 99%
“…It is important to consider that many NMSC appear on the face or visible areas of the skin. 2,9,10 QOL questionnaires have been used as an evaluation tool to quantify a particular health problem as well as utility weightings that quantify a preference for a particular health outcome. Most NMSC are treated with surgery, disrupting the normal activities of daily living, and have a financial impact, and repeated treatments may be needed in the setting of incomplete surgical margins or recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…S. Cancer Statistics Working Group, 2016), are increasing at 3% per year. Nearly 5 million cases of non-melanoma skin cancer (NMSC) occur annually,(American Cancer Society, 2016) creating substantial disfigurement (Bariani et al, 2006; Essers et al, 2007; Girschik et al, 2008; Hannuksela-Svahn et al, 1999) and healthcare costs. (Bickers et al, 2006) Exposure to solar and ultraviolet radiation (UV) is a primary cause.…”
Section: Introductionmentioning
confidence: 99%
“…This can lead to significant cosmetic disfigurement, especially when the face is involved. 5,8 Incomplete excision remains a frustrating problem because it leads to a significant reoperation rate or prolonged follow-up, with concomitant patient discomfort and economic impact. 1,3Y5 A wide range of different treatments has been described for the management of BCCs, but conventional surgical excision is the treatment of choice for primary BCCs and is appropriate for most of the these tumors.…”
mentioning
confidence: 99%